Graft Outcome of Corneal Patch for Perforated Corneal Ulcer - Apriwan D; Vitresia H; Anggraini R (HM Publisher, 2023)
Background: Corneal patch graft (CPG) is a part of the tectonic penetrating keratoplasty procedure performed on the perforated corneal ulcer. This procedure involves filling affected areas with full or partial-thickness cornea donors. This study aimed to determine the clinical results of corneal patch grafts in perforated corneal ulcers. Methods: A retrospective study assessing clinical results of CPG on the perforated corneal ulcer with iris prolapse. Clinical assessments include graft condition, anterior chamber depth (ACD), and visual acuity after surgery, with a follow-up duration of up to 8 weeks. Results: Twenty-one cases of perforated corneal ulcer with iris prolapse in 15 males (71.4%) and 6 females (28.6%). Locations of ulcer are peripheral and paracentral corneal. Visual acuity showed around light perception (LP) to 0.4. The most common etiology for corneal ulcers was infection (88.9%), followed by non-infection (Mooren’s ulcer) (11.1%). The graft condition after surgery showed promising results in 18 cases (85.7%), infection in 1 case (4.8%), and melting in 2 cases (9.5%). Adequate ACD was obtained in 77.8% of cases. An increase in visual acuity was shown in 44.4% of cases, depending on the location and severity of the ulcer. Conclusion: A corneal patch graft is an appropriate choice in treating perforated corneal ulcers to maintain ocular integrity (tectonic keratoplasty). However, in non-infectious ulcers, this procedure has not shown a good result, which may be related to disease progressivity.